2000
DOI: 10.1002/(sici)1521-3765(20000218)6:4<618::aid-chem618>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Rhodium(0) Nanoparticles: A Reusable Hydrogenation Catalyst for Arene Derivatives in a Biphasic Water-Liquid System

Abstract: A colloidal system based on an aqueous suspension of rhodium(0) nanoparticles proved to be an efficient catalyst for the hydrogenation of arene derivatives under biphasic conditions. The rhodium nanoparticles (2 ± 2.5 nm) were synthesized by the reduction of RhCl 3´3 H 2 O with sodium borohydride and were stabilized by highly watersoluble N-alkyl-N-(2-hydroxyethyl)ammonium salts (HEA-C n ). These surfactant molecules were characterized by measurements of the surface tension and the aqueous dispersions with rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 4 publications
5
89
0
1
Order By: Relevance
“…Supported and unsupported catalysts have been widely investigated over the last 80 years or more, [2] and it is unlikely that further major improvements in the economic and energy efficiencies of the process can be realized with conventional catalysts. It has been reported that soluble nanoclusters [3] in ionic liquids [4] or liquid water [5] exhibit excellent catalytic performance in the hydrogenation of various organic substrates and also are comparatively green in nature. It has been reported that soluble nanoclusters [3] in ionic liquids [4] or liquid water [5] exhibit excellent catalytic performance in the hydrogenation of various organic substrates and also are comparatively green in nature.…”
mentioning
confidence: 99%
“…Supported and unsupported catalysts have been widely investigated over the last 80 years or more, [2] and it is unlikely that further major improvements in the economic and energy efficiencies of the process can be realized with conventional catalysts. It has been reported that soluble nanoclusters [3] in ionic liquids [4] or liquid water [5] exhibit excellent catalytic performance in the hydrogenation of various organic substrates and also are comparatively green in nature. It has been reported that soluble nanoclusters [3] in ionic liquids [4] or liquid water [5] exhibit excellent catalytic performance in the hydrogenation of various organic substrates and also are comparatively green in nature.…”
mentioning
confidence: 99%
“…Since 2000, more than one hundred compounds have been synthesized and evaluated as protective agents of metal nanospecies according to their modulations. From surface tension measurements, most of these ionic salts display a surfactant behavior, and self‐aggregate above the critical micellar concentration (cmc) 52,57–58. The ammonium surfactants were efficiently used as capping agents of various transition metals (Ru, Rh, Pd, Ir, Pt, Au) in water.…”
Section: Metal Nps In Aqueous Media: Relevant Tools For Polyphasic Camentioning
confidence: 99%
“…Colloidal suspensions of Rh(0) were easily prepared by chemical reduction of rhodium trichloride, with sodium borohydride, in the presence of the ammonium stabilizer. An optimized [Surfactant]/[Rh] molar ratio of 2 proved to be relevant to avoid aggregation of the particles and to achieve significant catalytic activity 52. In the HEA series, in combination with the hydroxylated polar head, a C16 lipophilic chain provides the most suitable electrosteric stabilization 15.…”
Section: Metal Nps In Aqueous Media: Relevant Tools For Polyphasic Camentioning
confidence: 99%
See 1 more Smart Citation
“…Full conversion with 100% selectivity to methyl-cyclohexanecarboxylate (8a) required 60 °C and 10 bar H 2 . 75 On the other hand, low rates observed for EDG groups have been attributed to the higher energy barrier toward hydrogenation due to π-complexation of the aromatic ring. Ring deactivation effect and scarce resistance of ketonic group toward reduction was confirmed by the hydrogenation of 10 which provided cyclohexyl(phenyl)methanone (10a) in 1.3% yield under the above conditions.…”
Section: Catalyst Scope: Hydrogenation Of Arenesmentioning
confidence: 99%